FORM AND SYMBOLIC MEANING OF THE “SUBAMA BATIK” BATIK MOTIF BAJING KULON VILLAGE KROYA DISTRICT CILACAP REGENCY - Wahyu Haryana, Rizma (Universitas Negeri Semarang, 2025)
Batik is a cultural heritage that has deep aesthetic and symbolic value. This research aims to analyze the form and symbolic meaning of batik motifs produced by